Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.48550/arxiv.2104.09495
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kinematics and Star Formation of High-Redshift Hot Dust-Obscured Quasars as Seen by ALMA

Tanio Diaz-Santos,
Roberto J. Assef,
Peter R. M. Eisenhardt
et al.

Abstract: Hot, dust-obscured galaxies (Hot DOGs) are a population of hyper-luminous obscured quasars identified by WISE. We present ALMA observations of the [C ii] 158 µm fine-structure line and underlying dust continuum emission in a sample of seven of the most extremely luminous (EL; L bol ≥ 10 14 L ) Hot DOGs, at redshifts z 3.0-4.6. The [C ii] line is robustly detected in four objects, tentatively in one, and likely red-shifted out of the spectral window in the remaining two based on additional data. On average, [C … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 144 publications
0
5
0
Order By: Relevance
“…Hence, dust scattering from the former should dominate over free electrons unless the scattering medium is very dustdeficient. We expect dust to be present in significant quantities in the ISM of the host galaxy as, by selection, Hot DOGs have bright dust emission in the mid-IR and are typically well detected in the far-IR (Jones et al 2014;Wu et al 2014;Diaz-Santos et al 2021) 4 . Hence, the Thomson scattering scenario would only be plausible if the scattering medium is within the dust sublimation radius of the accretion disk, which we estimate to be 8.7 pc using equation ( 1) of Nenkova et al (2008) and the bolometric luminosity of W0116-0505 measured by Tsai et al (2015), adjusted for the differences in the cosmological model assumed.…”
Section: Thomson Scatteringmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, dust scattering from the former should dominate over free electrons unless the scattering medium is very dustdeficient. We expect dust to be present in significant quantities in the ISM of the host galaxy as, by selection, Hot DOGs have bright dust emission in the mid-IR and are typically well detected in the far-IR (Jones et al 2014;Wu et al 2014;Diaz-Santos et al 2021) 4 . Hence, the Thomson scattering scenario would only be plausible if the scattering medium is within the dust sublimation radius of the accretion disk, which we estimate to be 8.7 pc using equation ( 1) of Nenkova et al (2008) and the bolometric luminosity of W0116-0505 measured by Tsai et al (2015), adjusted for the differences in the cosmological model assumed.…”
Section: Thomson Scatteringmentioning
confidence: 99%
“…A similar scenario has been recently suggested by Lansbury et al (2020) and Jun et al (2021) based on estimates of the radiation feedback in luminous obscured quasars. Recently, Diaz-Santos et al (2021) has suggested that the availability of gas at large scales may lead to Hot DOGs being a recurring phase throughout the evolution of massive galaxies, with each episode perhaps leading to a BHD/ERQ/heavily reddened type 1 quasar phase as well, while the massive outflows slowly deplete the gas available in the ISM of their host galaxies.…”
Section: A Potential Relation Between Bhds Erqs Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Eisenhardt et al 2012;Wu et al 2012;Tsai et al 2015). Similar to COS-87259, these lower-redshift hot DOGs are found to possess very large stellar mass (log (M * /M )∼11-12), heavily obscured AGN, and often recent intense starbursts (SFR∼200-3000 M yr −1 ; Assef et al 2015;Diaz-Santos et al 2021). The SED shape of COS-87259 at rest-frame ≈3-100𝜇m is also consistent with that of known hot DOGs (Fig.…”
Section: Physical Interpretation Of the Multi-wavelength Sedmentioning
confidence: 66%
“…The population of z 6 quasars known to date are mostly non-obscured type I quasars (see discussion in Connor et al 2019;Vito et al 2019;Connor et al 2020;Vito et al 2021). This is likely due to a bias against obscured quasars in the selection process of z > 6 quasars, as observations have identified obscured quasars up to z ∼ 4.6 (e.g., Assef et al 2015;Vito et al 2020;Diaz-Santos et al 2021).…”
Section: Agn Luminositymentioning
confidence: 99%